2016
DOI: 10.1111/jvh.12615
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of resistance‐associated substitutions in acute hepatitis C virus infection by deep sequencing across six genotypes and three continents

Abstract: Several direct-acting antivirals (DAAs) have been approved for the treatment of chronic hepatitis C virus (HCV) infections, opening the door to highly effective interferon-free treatment regimens. Resistance-associated substitutions (RASs) have been reported both in treatment-naïve patients and following treatment with protease (NS3), phosphoprotein (NS5A) and polymerase (NS5B) inhibitors. The prevalence of naturally occurring RASs in untreated HCV-infected individuals has mostly been analysed in those infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
(44 reference statements)
3
12
0
Order By: Relevance
“…With regard to the RASs in NS5A, we showed that the NS5A domain was more conserved across GT1 to GT4 than the NS3 region. NS5A RASs were observed in 7/62 (11.3%) sequences, which is in line with the 6-16% reported in previous studies [19][20][21]. Carrasco et al [6], who explored NS5A RASs across different genotypes, showed that 36.1% of their patients had NS5A RASs.…”
Section: Discussionsupporting
confidence: 85%
“…With regard to the RASs in NS5A, we showed that the NS5A domain was more conserved across GT1 to GT4 than the NS3 region. NS5A RASs were observed in 7/62 (11.3%) sequences, which is in line with the 6-16% reported in previous studies [19][20][21]. Carrasco et al [6], who explored NS5A RASs across different genotypes, showed that 36.1% of their patients had NS5A RASs.…”
Section: Discussionsupporting
confidence: 85%
“…Sequencing was performed on the Illumina MiSeq platform. 29 In total 44 sequences were available for analysis, covering a range of HCV subtypes, including GT1a (n = 19), GT3a (n = 17), GT1b (n = 4), GT6a (n = 3) and GT2b (n = 1). E1E2 sequences were analysed for enrichment of amino acid residues in patients that mounted epitope-specific responses compared to those that did not, response was defined by the GT1 E1E2 mapped data.…”
Section: B Cell Immunodominance Is Associated With Antigenic Diversitymentioning
confidence: 99%
“…As a consequence of an error-prone viral polymerase, and a high replication rate, a swarm of mutations constantly get generated during HCV infection. Some of these natural mutations encode for RASs and have been reported in many studies in treatment-naïve patients 3 4 5 6 . Such naturally occurring RASs could negatively impact treatment success rates, particularly in patients with cirrhosis, those infected with genotype 3, and those who have failed interferon-based therapies.…”
mentioning
confidence: 99%